Mitigating Occupational Fraud: An Analysis of Fraudulent Actions, Opportunities, and Red Flags - Agrawal, Shashank (Digital Repository of Theses, 2024)
This dissertation delves into the dynamic nature of employee fraud in organizations and proposes strategies for prevention and detection. The study aims to address the question: How can organizations minimize employee fraud? Objectives include understanding fraud methods, identifying exploited weaknesses, and detecting early warning signs. This study features a qualitative approach based on content analysis of expert interviews discussing 157 real fraud conviction cases from the U.S. Department of Justice. The research advocates for an integrated approach to fraud prevention, combining theoretical insights with evidence-based strategies to protect organizational assets and integrity. It aims to advance academic discourse on employee fraud and concludes with a refined fraud model “Integrated Fraud Model (IFM)”, explaining fraud elements and their interplay in detail.